Predictors of immune reconstitution inflammatory syndrome associated with Kaposi's sarcoma: a case report. Issue 1 (December 2016) - Cattelan, Anna; Mattiolo, Adriana; Grassi, Angela; Piano, Maria; Sasset, Lolita; Trevenzoli, Marco; Zanovello, Paola; Calabrò, Maria
Abstract We present here a case of immune reconstitution inflammatory syndrome associated with Kaposi's sarcoma (KS-IRIS) developed in an AIDS patient two months after initiation of antiretroviral therapy (ART). Baseline characteristics of this IRIS-KS case, within a cohort of 12 naïve AIDS-KS patients, were analyzed. No statistically significant differences in CD4 cell counts, plasma HIV RNA load, KS clinical staging, human herpesvirus 8 (HHV8) antibody titers and HHV8 load in peripheral blood mononuclear cells and saliva were evidenced. HHV8 load in plasma was found to be significantly higher in the KS-IRIS patient (> 6 log10 genome equivalents/ml, p = 0.01, t– test) compared to the 11 patients with KS regression. This case highlights that measurement of HHV8 load in plasma may be useful to identify patients at risk for KS-IRIS, and that this parameter should be included in the design of larger studies to define KS-IRIS risk predictors.